Effectiveness of a cognitive intervention in executive functions to improve mental flexibility in children with attention deficit disorder and hyperactivity - Ríos-Gallardo, Ángela Magnolia; Hernández, Alfredis González; Toledo Nieto, Diana Carolina; Bermeo Losada, María Alejandra; Bonilla-Santos, Jasmín; Vallejo Cuéllar, Lísimaco (RFS Revista Facultad de Salud, 2016)
The Attention Deficit Hyperactivity Disorder (ADHD) is a behavioral syndrome that occurs in childhood, especially in the male population, is characterized by hyperactivity, impulsivity, and sometimes, accompanied by inattention and inappropriate operation according to the demands of the context. This behavior is more frequent in the school population, that has its beginning in childhood and it affects the activities of the child who suffers from it. It is quite probable that this affectation persists to throughout life, if not treated on time. It is estimated that 5.1 million children have a diagnosis of ADHD in the world. The global prevalence of this disorder ranges from 3% to 7%. Objective. To determine the effectiveness of a cognitive stimulation program in executive functions to improve mental flexibility in children with ADHD. Methodology. Type of quantitative study, quasi-experimental, with control group, pretest-training-postest. Materials and methods: The participants of the study were 51 children school age, 34 diagnosed with ADHD (experimental group) and 1 7 children who do not present any symptoms that suggests behavioral alterations (control group) Results. The experimental group showed to benefit from training and this evidence the significant gain with respect to the control group in tests that measure the executive system.